TINJAUAN IMPLEMENTASI PROSEDUR PEMBIAYAAN MURABAHAH UNTUK MENINGKATKAN PROFITABILITAS BPRS AMANAH UMMAH LEUWILIANG BOGOR - Ramadhan, Rian Tri; Trihantana, Rully; Kusumaningrum, Ria (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
In the implementation of Islamic financing, there are procedures that must be applied, one of which is the procedure for financing customer analysis, an analysis with feasibility studies, and paying attention to Sharia aspects. The purpose of this study is to review the efforts of Bank Pembiayaan Rakyat Syariah (BPRS) Amanah Ummah in implementing procedures in murabahah financing activities. This study uses a qualitative method. The results of this study indicate that BPRS Amanah Ummah applies a mixed procedure for financing customer analysis, namely between the 5C analysis (character, capacity, capital, collateral, condition) and analysis with feasibility studies (considering legal, market and marketing, financial, operational/technical, management, economic and social aspects, and environmental impact (AMDAL)), while also paying attention to Sharia aspects.